2004
DOI: 10.1055/s-2004-827212
|View full text |Cite
|
Sign up to set email alerts
|

Gastroprotective Effect of the Mixture of α- and β-Amyrin fromProtium heptaphyllum: Role of Capsaicin-Sensitive Primary Afferent Neurons

Abstract: This investigation evaluated the role of capsaicin-sensitive afferent neurons in the gastroprotective effect of alpha- and beta-amyrin, a triterpenoid mixture isolated from Protium heptaphyllum resin. Gastric mucosai damage was induced in mice by intragastric ethanol and assessed by planimetry. Mice pretreated orally with the amyrin mixture (50 and 100 mg/kg) or capsaicin (2.5 and 5 mg/kg), the pungent principle from red hot peppers, showed a significantly lower intensity of ethanol-associated gastric mucosal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
31
0
5

Year Published

2006
2006
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(39 citation statements)
references
References 7 publications
3
31
0
5
Order By: Relevance
“…7,8) Chemically, the a-and b-amyrin is a mixture of two triterpenes belonging to the ursane (a-amyrin) and oleanane (b-amyrin) series. Oleanolic acid is a pentacyclic triterpene that pertains to oleanane (b-amyrin) series (Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…7,8) Chemically, the a-and b-amyrin is a mixture of two triterpenes belonging to the ursane (a-amyrin) and oleanane (b-amyrin) series. Oleanolic acid is a pentacyclic triterpene that pertains to oleanane (b-amyrin) series (Fig.…”
mentioning
confidence: 99%
“…6) The natural triterpenic mixture a-and b-amyrin, isolated from Protium heptaphyllum has recently been shown to exert gastroprotective effect against ethanolinduced lesions and an antinociceptive effect in the visceral model of nociception induced by capsaicin, possibly involving the capsaicin-sensitive sensory afferents. 7,8) Chemically, the a-and b-amyrin is a mixture of two triterpenes belonging to the ursane (a-amyrin) and oleanane (b-amyrin) series. Oleanolic acid is a pentacyclic triterpene that pertains to oleanane (b-amyrin) series ( Fig.…”
mentioning
confidence: 99%
“…Chemical investigations have revealed the presence of β-amyrin and pharmacological studies of Protium heptaphyllum have revealed its anti-inflammatory, anti-pruritic, gastroprotective and hepatoprotective effects (Oliveira et al, 2004a;2004b;Holanda Pinto et al, 2008). Also, a few other studies have shown its efficacy in suppressing acute visceral and/or orofacial nociception and bladder inflammation (Lima-Júnior et al, 2007;Holanda Pinto et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…These results indicate that the antinociceptive potential of a-and b-amyrin, main components of the resin, possibly involves the opioid and vanilloid receptor mechanisms (Oliveira et al, 2005;Lima-Junior et al, 2006). Furthermore, the gastro-protective mechanisms of the a-and b-amyrin mixture involves, at least in part, the activation of capsaicin-sensitive primary afferent neurons (Oliveira et al, 2004).…”
Section: Introductionmentioning
confidence: 80%